Android–Based “EDUGARLIN” Application in Increasing Knowledge and Attitudes of Postpartum Mother about Postpartum Fitness - Junengsih, Junengsih; Jehanara, Jehanara; Fitriana, Shentya; Siregar, Mukhlidah Hanum (Poltekkes Kemenkes Jakarta III, 2023)
Knowledge of postpartum fitness includes recognising the danger signs of childbirth, fulfilling nutrition, the physical adaptation of postpartum and breastfeeding mothers, the process of achieving the role of motherhood, adaptation to becoming parents, health promotion for healthy living behaviour, prevention of diseases and complications of puerperium, family planning and the success of exclusive breastfeeding are critical things that postpartum mothers should know. Information technology from smartphones using Android-based applications can be used to increase mothers' knowledge about postpartum fitness. This study aims to analyse the differences in knowledge and attitudes of postpartum mothers to improve postpartum fitness before and after being given the